Cardioproteção promovida pelo mirtenol na lesão de isquemia-reperfusão é mediada por ações antioxidantes e antiapoptóticas - Britto, Raquel Moreira de (2018)
Cardiovascular diseases are the leading cause of death worldwide, and myocardial infarction (MI) is one of the most devastating. Cardiac ischemia-reperfusion injury represents a major threat to human health, contributing to adverse cardiovascular effects.However, although reperfusion of the ischemic heart is essential to reduce myocardial damage, restoration of blood flow may, paradoxically, amplify cellular damage.The recognition that pathological events occurring both in ischemia and reperfusion contribute to tissue injury leads to accelerated efforts to identify mechanisms of IR injury in the hope of identifying new treatments that may limit injury induced by blood reduction flow and / or damage produced by reperfusion.Myrtenol is a monoterpene with multiple pharmacological activities. However, although monoterpenes have been proposed to play beneficial roles in a variety of cardiac disorders, pharmacological actions of myrtenol in the heart are not yet reported. Hence, the aim of this study was to evaluate whether myrtenol promotes cardioprotection against myocardial ischemia-reperfusion (IR) injury, and the mechanisms involved in these effects. Male Wistar rats were orally treated for seven consecutive days with solution (NaCl 0.9% 0.20 ml + DMSO 0.05 ml), myrtenol (50 mg/kg) or N-acetyl cysteine (1.200 mg/kg, NAC).Subsequently, the hearts were submitted to cardiac IR injury, through the aortic perfusion flow system of the langedorff type, contractile parameters such as left ventricular pressure (PVE), maximum rise/down velocity of left intraventricular pressure (dP/dt), heart rate (HR), electrocardiographic parameters, HR, PR interval and duration of the QRS complex, measured the activity of Lactate Dehydrogenase (LDH), determined the severity of cardiac arrhythmias (ASI). The oxidative stress was evaluated on the basis of the determination of total hydroperoxides, total sulfhydryl (SH) groups, measurements of the reactive oxygen species (ROS) generation, the carbonylated proteins, the activity of the endogenous antioxidant enzymes: superoxide dismutase (SOD), catalase (CAT) , glutathione peroxidase (GPx) and glutathione reductase (GR), and the infarct area. The apoptosis pathway was investigated by the expression of Bax and Bcl-2 proteins and in situ apoptosis was studied from the TUNEL assay. Here, we show that the severe impairment of contractile performance induced by IR was significantly prevented by myrtenol or NAC. Moreover, Myrtenol abolished aberrant electrocardiographic waveform (ST-segment elevation), as well as reduced life-threatening arrhythmias and infarct size induced by IR injury. Importantly, myrtenol fully prevented the massive increase of cardiac reactive oxygen species generation and oxidative stress damage. Accordingly, myrtenol restored the impairment of endogenous antioxidant enzymes (superoxide dismutase, catalase, glutathione peroxidase and reductase) activities and balance of pro- and anti-apoptotic pathways (Bax and Blc-2), associated with decreased TUNEL-positive apoptotic cells. Taken together, our data show that myrtenol promotes cardioprotection against IR injury through attenuation of oxidative stress and inhibition of pro-apoptotic pathway.